Determining university students' cognitive structures and alternative concepts on striated muscle by word association test - Abdulkadir Akatan; Mehmet Kılıç; Zeliha Baştürk; Nuri M. Embiyaoğlu (Physical Education of Students)
Background and Study Aim. Muscles are a set of topics for physical education and sports. Cognitive structure and alternative concepts of students should be diagnosed about striated muscles, which are very rich in terms of abstract concepts. The aim of this research is to determine the cognitive structures, alternative concepts and conceptual change process of university students on striated muscle with the word association test.